Population Growth, Jobs Growth and Commuting Flows in Melbourne - Johnson, Leanne; Malam, Karen; de Silva, Hema (Bureau of Infrastructure, Transport and Regional Economics, 2011)
This report identifies recent spatial changes in employment and the residential population within Melbourne, and investigates how commuting behaviour has responded to these changes. It also explores the extent to which the city’s spatial development and commuting patterns have been reshaped in the direction envisaged by recent metropolitan plans.
Keywords: Housing, communities and neighbourhoods; Labour market; Housing, communities and neighbourhoods; Employment and unemployment